Pengaruh Dukungan Sosial Terhadap Stres Kerja pada Pekerja Generasi Z di Karawang - Shinta Dewi Lestari Tulus; Arif Rahman Hakim; M Choirul Ibad (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the influence of social support on work stress among Gen Z workers in Karawang. Gen Z is known as a generation that is highly adaptive to technology but also vulnerable to work-related pressures and emotional challenges in the workplace. This research employs a quantitative approach with a snowball sampling. A total of 392 respondents participated in the study, selected using the snowball sampling technique. The instruments used were the Perceived Stress Scale (PSS-10) to measure work stress and the Multidimensional Scale of Perceived Social Support (MSPSS) to assess social support. Data analysis was conducted using simple linear regression with the assistance of SPSS version 25.0. The regression analysis showed a significant influence of social support on work stress, with a significance value of 0.006 (p < 0.05). The coefficient of determination (R²) was 0.019, indicating that social support contributed 1.9% to work stress. These findings suggest that higher levels of perceived social support are associated with lower levels of work stress among Gen Z workers. This study emphasizes the importance of fostering a supportive work environment to reduce psychological pressure on younger generations in the workforce.